2021
DOI: 10.3390/app11094306
|View full text |Cite
|
Sign up to set email alerts
|

Color Texture Image Complexity—EEG-Sensed Human Brain Perception vs. Computed Measures

Abstract: In practical applications, such as patient brain signals monitoring, a non-invasive recording system with fewer channels for an easy setup and a wireless connection for remotely monitor physiological signals will be beneficial. In this paper, we investigate the feasibility of using such a system in a visual perception scenario. We investigate the complexity perception of color natural and synthetic fractal texture images, by studying the correlations between four types of data: image complexity that is express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 78 publications
(90 reference statements)
1
4
0
Order By: Relevance
“…The very slight changes in the correlation coefficients (r) in Figure 17 indicate that the number of frequencies (n F ) chosen to design the Gabor filter bank seems to have had little impact on image texture detection by the filter bank. A similar observation was made by Bianconi and Fernandez [34] for texture classification using Gabor filtering. They demonstrated that the number of frequencies and orientations used to design the filter bank did not significantly affect the accuracy of texture classification.…”
Section: Gabor Featuressupporting
confidence: 82%
See 2 more Smart Citations
“…The very slight changes in the correlation coefficients (r) in Figure 17 indicate that the number of frequencies (n F ) chosen to design the Gabor filter bank seems to have had little impact on image texture detection by the filter bank. A similar observation was made by Bianconi and Fernandez [34] for texture classification using Gabor filtering. They demonstrated that the number of frequencies and orientations used to design the filter bank did not significantly affect the accuracy of texture classification.…”
Section: Gabor Featuressupporting
confidence: 82%
“…For the Gabor features, a bank of 36 Gabor filters were designed using six frequencies (n F = 6) (i.e., F ∈ {1, 0.7, 0.5, 0.35, 0.25, 0.18} with the maximum frequency F m = 1) and six orientation angles (n O = 6) i.e., θ ∈ {0, 30, 60, 90, 120, 150} • (see Figure 3). As recommended in [34], the frequency ratio F r was half-octave frequency spacing (F r = √ 2) and the smoothing parameters were γ = η = 0.5. The mean and standard deviation of the energy of the filtered images were averaged over the six orientation angles to obtain the rotation-invariant Gabor features of the textile images.…”
Section: Computing the Image Descriptors And Texture Features Of The ...mentioning
confidence: 99%
See 1 more Smart Citation
“…Where pi is the probability of appearance of pixel value i in the image and N the amount of possible pixel values. Besides that, according to Nicolae and Ivanovici [13], many different entropy types and optimised versions have emerged in recent years, each with its own set of advantages, such as multi-scale entropy, cross entropy, fuzzy entropy, and many more when considering spatial information, with additional applications in the biomedical imaging domain.…”
Section: Methodsmentioning
confidence: 99%
“…According to Nicolae and Ivanovici [13], fractal dimension is the most representative measure for expressing the fractal geometry of colour texture images. The fractal dimension expresses texture variations and irregularities in relation to self-similar regions observed across different size scales.…”
Section: Methodsmentioning
confidence: 99%